2021
DOI: 10.2514/1.j059284
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Surface Pressure Fluctuations on an Airbus-A320 Fuselage at Cruise Conditions

Abstract: The fuselage surface pressure fluctuations on an Airbus-A320 aircraft at cruise conditions are simulated by solving a Poisson equation. The right-hand-side source terms of the Poisson equation, including both the mean-shear term and the turbulence-turbulence term, are realized with synthetic turbulence generated by the Fast Random Particle-Mesh Method. The stochastic realization is based on time-averaged turbulence statistics derived from a RANS simulation under the same condition as in the flight tests, condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…where the pre-factor c τ needs to be empirically determined. By comparing the streamwise coherence of wall pressure fluctuations, Hu et al 28,29 suggested c τ = 1.2 and 2.5. The former value was determined with a wall pressure fluctuations simulation for a low Reynolds number ZPG flow, and the latter for an aircraft fuselage flow at cruise conditions.…”
Section: Methods and Mean Flow Conditionsmentioning
confidence: 99%
“…where the pre-factor c τ needs to be empirically determined. By comparing the streamwise coherence of wall pressure fluctuations, Hu et al 28,29 suggested c τ = 1.2 and 2.5. The former value was determined with a wall pressure fluctuations simulation for a low Reynolds number ZPG flow, and the latter for an aircraft fuselage flow at cruise conditions.…”
Section: Methods and Mean Flow Conditionsmentioning
confidence: 99%